2013
DOI: 10.1371/journal.pone.0061657
|View full text |Cite
|
Sign up to set email alerts
|

On the Respiratory Mechanics Measured by Forced Oscillation Technique in Patients with Systemic Sclerosis

Abstract: BackgroundPulmonary complications are the most common cause of death and morbidity in systemic sclerosis (SSc). The forced oscillation technique (FOT) offers a simple and detailed approach to investigate the mechanical properties of the respiratory system. We hypothesized that SSc may introduce changes in the resistive and reactive properties of the respiratory system, and that FOT may help the diagnosis of these abnormalities.Methodology/Principal FindingsWe tested these hypotheses in controls (n = 30) and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 58 publications
14
35
0
Order By: Relevance
“…Other authors, investigating early changes in sarcoidosis, found results similar to our findings [28]. These results are also consistent with those observed in systemic sclerosis [23], silicosis [29] and smoking [77]. In subjects with coal mining-related pneumoconiosis, a pattern of reticular nodulation on the chest radiograph was reported, representing the initial stage of dust deposition in the lung.…”
Section: Discussionsupporting
confidence: 92%
“…Other authors, investigating early changes in sarcoidosis, found results similar to our findings [28]. These results are also consistent with those observed in systemic sclerosis [23], silicosis [29] and smoking [77]. In subjects with coal mining-related pneumoconiosis, a pattern of reticular nodulation on the chest radiograph was reported, representing the initial stage of dust deposition in the lung.…”
Section: Discussionsupporting
confidence: 92%
“…This variable represents the total mechanical load of the respiratory system and is associated with respiratory work. In this study, Z4Hz mainly describes the effect resulting from the total resistance and compliance of the respiratory system [15]. …”
Section: Methodsmentioning
confidence: 99%
“…The total mechanical load, described by Z4Hz, may be related to the increase in respiratory work, fatigue and shortness of breath typical in COPD patients [15,35,36]. The control group exhibited little variation (fig.…”
Section: Impedance Modulusmentioning
confidence: 99%
“…These characteristic were important to explore lung function in children with CF [ 6 - 11 ]. Recently, this technique was successfully applied in our laboratory to study the early respiratory changes in smokers [ 12 ] and patients with sarcoidosis [ 13 ] and systemic sclerosis [ 14 ]. Compartmental models of the multi-frequency impedance allowed a detailed description of the human respiratory system by equivalent electrical circuits [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%